2015
DOI: 10.1002/cb.1561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different packages on food product contagion: The moderating roles of mood states and product‐related information

Abstract: Across two experiments conducted for this research, it is evident that different moderators do play a role in the influence of food product contagion effects. This research focuses on how mood states or product-related information moderate contagion prime and package type. Existing studies indicate that unsealed packages can enhance the extent of the contagion effects more than sealed packages. Study 1 showed that happy people experienced stronger positive contagion effects than sad or neutral ones and that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Thus, higher compensation was required to compensate for the loss of value. This is consistent with the findings of Siegrist and Cvetkovich [42], Fox, Hayes, and Shogren [26], and Lin and Shih [43]. To identify whether the bids were stable over the nine trials, we also divided the mean bids by the standard deviation in each trial, and the result shows that the bids tend to stabilize in Trials 7 and 8.…”
Section: Resultssupporting
confidence: 85%
“…Thus, higher compensation was required to compensate for the loss of value. This is consistent with the findings of Siegrist and Cvetkovich [42], Fox, Hayes, and Shogren [26], and Lin and Shih [43]. To identify whether the bids were stable over the nine trials, we also divided the mean bids by the standard deviation in each trial, and the result shows that the bids tend to stabilize in Trials 7 and 8.…”
Section: Resultssupporting
confidence: 85%
“…Within the persuasion literature, positive (vs. negative) emotions, such as happiness (vs. sadness), have been shown to lead to more positive attitudes (Petty, Leandre Fabrigar, & Duane, ). Thus, positive emotions tend to favorably impact evaluations of people, objects (Adaval, ; Meloy, ; Mogilner et al, ), and even the experience with a product (Lin & Shih, ). Consistently, Williams and Aaker () have shown that persuasive appeals with mixed emotions might harm (rather than help) attitude toward the brand.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Past research has shown that psychological influence plays a role in consumer purchase process activities such as information processing (of foreign and local cues on packaging), value formation (associating Westernisation with cues) and choice decision (purchase of a product in either packaging) (Yi- Cheon Yim et al, 2014;Bartsch et al, 2015). When consuming products, consumers seek congruence between their perceptions of the product and their personal values (Limon et al, 2009;Lin and Shih, 2015). This implies that consumers' preference for a particular packaging type (i.e.…”
Section: Discussionmentioning
confidence: 99%